(untitled) (Prilozi za orijentalnu filologiju, 2017)
A certain number of Arabic words has come into Serbo-Croatian through various European languages. One part of therm consists of direct borrowings from the Arabic, a small number of them has come via Persian, and most of therm have most probably come via Turkish. This is quite obvious considering the fact that there are many Arabic loanwords in the Turkish language, on the one hand, and that, on the other, the Turks were for many centuries rulers in these parts. That is why it has been in a way a justifiable practice to include Arabic loanwords as a matter of course among the Turkish loanwords, although there is a comparatively considerable number of Arabic words among them. So, for example, out of some 6.500 “Turkish borrovvings”, entered in the latest and the biggest dictionary of its kind published in Yugoslavia, compiled by Abdulah Škaljić (see Footnote 4 of this paper), 3.800 entries are in fact of Arabic origin. Most of our Müslim personal names are of Arabic origin. The position is similar with words concerning the religious life of Muslims, but besides these there is a great number of Arabic borrowings denoting ideas from the most diverse provinces of life in general. This paper deals mainly with the phonetic changes which the Arabic borrowings have undergone, vvhether at the time they čame into Serbo-Croatian or in the language through which they čame or both. In the chapter dealing with the consonants of the Arabic borrowings the most significant substitutes for Arabic consonants in Serbo-Croatian, cognate and otherwise, are cited. They are listed according to physiological groups, defined by the place of their articulation, beginning with labials and ending with laryngals. Under separate headings items such as the loss, addition, insertion, metathesis, assimilation and dissimilation, and palatalisation of consonants of the Arabic borrovvings are discussed. Then the changes in the vowel system in the Arabic loanvvords are discussed, then follow examples of the most important phenomena concerning Arabic vowels, such as assimilation, dissimilation, insertion, addition and loss, changes of their quality and lastly come some remarks about the accent in the Arabic loanwords. The next chapter gives a short outline of new formations with Arabic borrovvings, first those made by means of derivation with suffixes and prefixes from Serbo-Croatian and some other languages. Then are given briefly the most characteristic ways of compounding Arabic loanvvords with Serbo- Croatian, Turkish and Persian words. Under shorter separate headings there are remarks on some syntactic and semantic characteristics of Arabic borowings. At the end of the paper a point is made about the need to collect Arabic loanwords (perhaps within the framework of Turkish borrowings) in ali those parts of the country where they occur, and in the whole of Yugoslav literature, because they have not been colleced completely, much less studied, and because they have been progressively going out of use and have become archaic in spoken as well as in written language. Moreover, the collection and study of Arabic loanvvords in Serbo-Croatian vvould be interesting from the point of view of Arabic itself, because the Arabic element in our language accounts not only for the influence that the Arabic language has had, but also for the influence of Arabic and moreover Islamic culture in general.